BÀI 1 : tìm x
A) ( 2x -1 ) 10 = 49 5
bài 1 : Tìm x
a) 5 + ( x + 27 ) = 64
b) 64 - ( x - 2 ) = 25
c) 7 - ( x + 5 ) + 14 = 343
d) 5 . x - 25 = 10
e) 4 . ( x - 5 ) - 8 = 48
f) 49 - ( 15 + x ) = 12
g) 49 - 7. ( 13 - x ) = 14
h) 155 - 10. ( x + 1 ) = 55
5 + ( x + 27 ) = 64
( x + 27 ) = 64 - 5 ( x + 27 ) = 59 x = 59 - 27 x = 32a) \(\Rightarrow x+27=59\Rightarrow x=32\)
b) \(\Rightarrow x-2=39\Rightarrow x=41\)
c) \(\Rightarrow x+5=-322\Rightarrow x=-327\)
d) \(\Rightarrow5x=35\Rightarrow x=7\)
e) \(\Rightarrow4\left(x-5\right)=56\Rightarrow x-5=14\Rightarrow x=19\)
f) \(\Rightarrow15+x=37\Rightarrow x=22\)
g) \(\Rightarrow7\left(13-x\right)=35\Rightarrow13-x=5\Rightarrow x=8\)
h) \(\Rightarrow10\left(x+1\right)=100\Rightarrow x+1=10\Rightarrow x=9\)
Bài 10 Tìm x
a/ (2x–5)x2x2 –4x(x–3)= 0
b/ (x–1) x2x2 +(x+6)(3–x)= –1
c/ (3x+1)x2x2 –9x(x–1)= 0
d/ (x–5)x2x2 –(x–4)(x–1)= 10
bài 1 :tìm x,y biết
a) (5x+1)=\(\dfrac{36}{49}\) b) (x-2/9) = (2/3) c)(8x-1) 2x+1= 5^2 x+1
d) (x-3,5)^x+(y - 1/10)^4=0
`(5x+1)=36/49`
`<=> 5x = 36/49-1`
`<=> 5x = -13/49`.
`<=> x = -13/245.`
Vậy `x = -13/245`.
`b, x-2/9 = 2/3`.
`<=> x = 2/3 + 2/9`
`<=> x = 8/9`.
Vậy `x = 8/9`.
c: (8x-1)^(2x+1)=5^(2x+1)
=>8x-1=5
=>8x=6
=>x=3/4
d: Sửa đề: (x-3,5)^2+(y-1/10)^4=0
=>x-3,5=0 và y-0,1=0
=>x=3,5 và y=0,1
tìm x
a,(x+1)^3-(x-1)^3-6(x-1)^2=-10
b,x(x+5)(x-5)-(x+2)(x^2-2x+4)=42
c,(x-2)^3-(x-3)(x^2+3x+9)+6(x+1)^2=49
a) \(\left(x+1\right)^3-\left(x-1\right)^3-6\cdot\left(x-1\right)^2=10\)
\(\Rightarrow x^3+3x^2+3x+1-x^3+3x^2-3x+1-6\cdot\left(x^2-2x+1\right)=10\)
\(\Rightarrow6x^2+2-6x^2+12x-6=10\)
\(\Rightarrow12x-4=10\)
\(\Rightarrow12x=14\)
\(\Rightarrow x=\dfrac{7}{6}\)
b) \(x\left(x+5\right)\left(x-5\right)-\left(x+2\right)\left(x^2-2x+4\right)=42\)
\(\Rightarrow x\left(x^2-25\right)-\left(x^3+8\right)=42\)
\(\Rightarrow x^3-25x-x^3-8=42\)
\(\Rightarrow-25x-8=42\)
\(\Rightarrow-25x=50\)
\(\Rightarrow x=\dfrac{50}{-25}=-2\)
c) \(\left(x-2\right)^3-\left(x-3\right)\left(x^2+3x+9\right)+6\left(x+1\right)^2=49\)
\(\Rightarrow x^3-6x^2+12x-8-\left(x^3-27\right)+6\left(x^2+2x+1\right)=49\)
\(\Rightarrow x^3-6x^2+12x-8-x^3+27+6x^2+12x+6=49\)
\(\Rightarrow24x+25=49\)
\(\Rightarrow24x=24\)
\(\Rightarrow x=\dfrac{24}{24}=1\)
Bài 1: Tìm x
a) 3(x-1)^2.3x(x-5)=0
b) (x+3)^2-5x-15=0
c) 2x^5-4x^3+2x=0
a) \(3\left(x-1\right)^2\cdot3x\left(x-5\right)=0\)
\(\Rightarrow9x\left(x-1\right)^2\left(x-5\right)=0\)
\(\Rightarrow\left[{}\begin{matrix}x=0\\x-1=0\\x-5=0\end{matrix}\right.\Rightarrow\left[{}\begin{matrix}x=0\\x=1\\x=5\end{matrix}\right.\)
b) \(\left(x+3\right)^2-5x-15=0\)
\(\Rightarrow\left(x+3\right)^2-5\left(x+3\right)=0\)
\(\Rightarrow\left(x+3\right)\left(x+3-5\right)=0\)
\(\Rightarrow\left(x+3\right)\left(x-2\right)=0\)
\(\Rightarrow\left[{}\begin{matrix}x+3=0\\x-2=0\end{matrix}\right.\Rightarrow\left[{}\begin{matrix}x=-3\\x=2\end{matrix}\right.\)
c) \(2x^5-4x^3+2x=0\)
\(\Rightarrow2x\left(x^4-2x^2+1\right)=0\)
\(\Rightarrow2x\left[\left(x^2\right)^2-2\cdot x^2\cdot1+1^2\right]=0\)
\(\Rightarrow2x\left(x^2-1\right)^2=0\)
\(\Rightarrow2x\left(x-1\right)^2\left(x+1\right)^2=0\)
\(\Rightarrow\left[{}\begin{matrix}x=0\\x-1=0\\x+1=0\end{matrix}\right.\Rightarrow\left[{}\begin{matrix}x=0\\x=1\\x=-1\end{matrix}\right.\)
\(\text{#}Toru\)
tìm x
a.(2x-5)^2=49
b.(2x+5)^2-(1-2x)^2=10
c.(9-2x)^3=27
a) \(\left(2x-5\right)^2=49\)
\(\left(2x-5\right)^2=\left(\pm7\right)^2\)
\(=>2x-5=7\) hoặc \(2x-5=-7\)
\(\cdot2x-5=7\) \(\cdot2x-5=-7\)
\(2x=5+7\) \(2x=-7+5\)
\(2x=12\) \(2x=-2\)
\(x=12:2\) \(x=-2:2\)
\(x=6\) \(x=-1\)
Vậy x=6 hoặc x=-1
b/ \(\left(2x+5\right)^2-\left(1-2x\right)^2=10\)
\(4x^2+20x+25-\left(1-4x+4x^2\right)=10\)
\(4x^2+20x+25-1+4x-4x^2=10\)
\(24x+24=10\)
\(24x=10-24\)
\(24x=-14\)
\(x=\frac{-14}{24}\)
\(x=\frac{-7}{12}\)
c/ \(\left(9-2x\right)^3=27\)
\(\left(9-2x\right)^3=3^3\)
\(9-2x=3\)
\(2x=9-3\)
\(2x=6\)
\(x=6:2\)
\(x=3\)
tìm x
(2x-1)10=495
Ta có
(2x-1)^10 = 49^5
=> (2x-1)^10 = (7^2)^5
=> (2x-1)^10 = 7^10
=> 2x-1 = 7
=> 2x= 8
=> x=4
(2x-1)10=495
=> (2x-1)10=(72)5=[(-7)2 ]5
=> (2x-1)10=710=(-7)10
=> 2x-1=7 hoặc 2x-1=-7
=> 2x=8 hoặc 2x=-6
=> x=4 hoặc x=-3
Bài 2: Tìm x
A) 2x+5/2=-3/5
B) 1/2:x-5/6=-2/3
C) (312-x):12,6=24,5
\(a,2x+\dfrac{5}{2}=-\dfrac{3}{5}\)
\(2x=-\dfrac{3}{5}-\dfrac{5}{2}\)
\(2x=-\dfrac{31}{10}\)
\(x=-\dfrac{31}{10}:2\)
\(x=-\dfrac{31}{20}\)
\(b,\dfrac{1}{2}:x-\dfrac{5}{6}=-\dfrac{2}{3}\)
\(\dfrac{1}{2}:x=-\dfrac{2}{3}+\dfrac{5}{6}\)
\(\dfrac{1}{2}:x=\dfrac{1}{6}\)
\(x=\dfrac{1}{2}:\dfrac{1}{6}\)
\(x=3\)
\(c,\left(312-x\right):12,6=24,5\)
\(312-x=24,5\times12,6\)
\(312-x=308,7\)
\(x=312-308,7\)
`x=3,3`
a: =>2x=-3/5-5/2=-6/10-25/10=-31/10
=>x=-31/20
b: =>1/2:x=-2/3+5/6=5/6-4/6=1/6
=>x=1/2:1/6=3
c: =>312-x=308,7
=>x=3,3
Bài 3 tìm x
a) (x-1)(x-5) 3=0
b) 3x^2+7x=10
`3(x-1)(x-5) =0`
`<=> (x-1) =0` hoặc `x-5 = 0`.
`<=> x =1` hoặc `x = 5`.
Vậy `x = 1` hoặc `x = 5.`
`b, 3x^2 + 7x = 10`.
`<=> 3x^2 + 7x - 10 = 0`
`<=> (3x+10)(x-1) =0`
`<=> 3x + 10 = 0` hoặc `x - 1=0`
`<=> x = -10/3` hoặc `x = 1.`
Vậy `x = -10/3` hoặc `x = 1.`